Use of Video-Apparatus during Monitoring of Conflict Situations in Road Traffic on Roundabout in the Czech Republic - Vladislav Krivda (Promet - Traffic&Transportation, 2013)
The wrong behavior of the road traffic participants is a permanently discussed issue in many countries with advanced road transport. Such behavior doesn’t always result in traffic accident, but only in restriction or danger of the culprit or other participants. For monitoring the behavior problems we can for example use the video-analysis of the conflict situations. The methodology of the conflict situations monitoring with the video-apparatus application is described in the paper presented. There are also results of the conflict situations analysis on the selected roundabouts in the Czech Republic. The paper refers to suitability of the conflict situations video-analysis application not only for monitoring the wrong behavior of drivers and other participants of road traffic, but also for monitoring the inappropriately designed building elements (this hypothesis is confirmed by results of research, which are shown this article).